2022
DOI: 10.1101/2022.06.12.22276088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Opaganib on Supplemental Oxygen and Mortality in Patients with Severe SARS-CoV-2 Pneumonia

Abstract: RationaleThere are few treatment options for severe COVID-19 pneumonia. Opaganib is an oral treatment under investigation.ObjectiveEvaluate opaganib treatment in hospitalized patients with severe COVID-19 pneumonia.MethodsA randomized, placebo-controlled, double-blind phase 2/3 trial was conducted in 60 sites worldwide from August 2020 to July 2021.Patients received either opaganib (n=230; 500mg twice daily) or matching placebo (n=233) for 14 days.Main Outcome MeasurementsPrimary outcome was the proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Therefore, opaganib was evaluated in patients hospitalized with severe COVID-19 pneumonia [71], including a Phase 2a study [72] and a Phase 2/3 multinational randomized, placebo-controlled study. These trials demonstrated the safety of opaganib and a clinical benefit to patients requiring oxygen supplementation of 60% or less (62% reduction in rate of ventilation and death) [73]. To date, more than 470 people have been treated with opaganib in oncology and COVID-19 clinical trials, demonstrating the excellent safety profile of the drug even in severely compromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, opaganib was evaluated in patients hospitalized with severe COVID-19 pneumonia [71], including a Phase 2a study [72] and a Phase 2/3 multinational randomized, placebo-controlled study. These trials demonstrated the safety of opaganib and a clinical benefit to patients requiring oxygen supplementation of 60% or less (62% reduction in rate of ventilation and death) [73]. To date, more than 470 people have been treated with opaganib in oncology and COVID-19 clinical trials, demonstrating the excellent safety profile of the drug even in severely compromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, opaganib has also shown excellent safety and preliminary efficacy in patients with compromised lung function. Specifically, a Phase 2/3 multinational randomized, placebo-controlled study demonstrated the safety of opaganib in patients hospitalized with severe COVID-19, and a clinical benefit to patients requiring oxygen supplementation of 60% or less (62% reduction in rate of ventilation and death) [54]. To date, more than 470 people have been treated with opaganib in oncology and COVID-19 clinical trials, demonstrating the excellent safety profile of the drug even in severely compromised patients.…”
Section: Discussionmentioning
confidence: 99%